A class of exactly solvable free-boundary inhomogeneous porous medium flows. - Howison, S; Loutsenko, I; Ockendon, J (2007)
We describe a class of inhomogeneous two-dimensional porous medium flows, driven by a finite number of multipole sources; the free boundary dynamics can be parametrized by polynomial conformal maps. © 2006 Elsevier Ltd. All rights reserved.